2010
DOI: 10.1007/978-3-642-13388-6_37
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motivational Learning Companions on Low Achieving Students and Students with Disabilities

Abstract: Abstract.We report the results of a randomized controlled evaluation of the effectiveness of pedagogical agents as providers of affective feedback. These digital learning companions were embedded in an intelligent tutoring system for mathematics, and were used by approximately one hundred students in two public high schools. Students in the control group did not receive the learning companions. Results indicate that low-achieving students-one third of whom have learning disabilities-had higher affective needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 9 publications
2
45
0
4
Order By: Relevance
“…Work with AutoTutor-AS revealed that only low knowledge students benefited from affect sensitivity (D'Mello and Graesser 2012a;D'Mello et al 2011b). This work mirrors findings with the Wayang Output tutoring system, which found that low knowledge students benefit more from affective support provided by animated agents (Woolf et al 2010). Similar results have been found for factors such as politeness of animated agents (Wang et al 2008).…”
Section: Discussion: Key Findings From Autotutorsupporting
confidence: 81%
“…Work with AutoTutor-AS revealed that only low knowledge students benefited from affect sensitivity (D'Mello and Graesser 2012a;D'Mello et al 2011b). This work mirrors findings with the Wayang Output tutoring system, which found that low knowledge students benefit more from affective support provided by animated agents (Woolf et al 2010). Similar results have been found for factors such as politeness of animated agents (Wang et al 2008).…”
Section: Discussion: Key Findings From Autotutorsupporting
confidence: 81%
“…Natural language processing (NLP) is clearly an AI area and many systems now try to do this (e.g., Person et al 2001;Wang et al 2011). Another use of AI is in trying to infer and respond to student emotion (e.g., Baker et al 2010;du Boulay et al 2010;D'Mello et al 2010;Woolf et al 2010). Still others have used speech recognition technology to try to better teach students (Chen et al 2011;Johnson 2010).…”
Section: Assistments and The Existing Aied Literaturementioning
confidence: 99%
“…They consist of the aspects of the visual and auditory presence of the APA that are hypothesized to ''make the learning experience more interesting, believable, or natural'' (p. 508). Empirical studies of these properties have explored the influence of the APA's age, gender, ethnicity, politeness, responsiveness, dynamism, and visual appeal, among others (e.g., André et al 1996;Arroyo et al 2011Arroyo et al , 2009Baylor 2011;Baylor and Kim 2004;Baylor and Ryu 2003;Craig et al 2002;Domagk 2010;Kim et al 2007;Lester et al 1997;Moreno 2004;Moreno et al 2000;Plant et al 2009;Wang et al 2008;Woolf et al 2010). Given our special interest in gender and science education, we summarize below the empirical studies that have investigated gender and motivation in relation to APAs in virtual science learning environments.…”
Section: Animated Pedagogical Agents and Student Motivationmentioning
confidence: 99%